Theories of developmental psychology - Miller, Patricia H. (New York Worth Publishers, 2002)
This book places the major theories of development in historical and contemporary context, and provides frameworks for understanding and perceiving the significance of the research findings in developmental psychology.
Piaget's cognitive-stage theory and the neo-Piagetians -- Freud's and Erikson's psychoanalytic theories -- Social learning theory -- Information-processing theory -- Ethology and other evolutionary theories -- Gibson's ecological theory of perceptual development -- Vygotsky and the sociocultural approach -- Contemporary minitheories and emerging approaches -- Reflections.
Includes bibliographical references (pages [458]-491) and indexes.
Keywords: Developmental psychology -- Philosophy; Child psychology -- Philosophy